2022
DOI: 10.1093/jee/toac131
|View full text |Cite
|
Sign up to set email alerts
|

Rosa chinensisCultivars Affect Fitness-Related Characteristics and Digestive Physiology of the Western Flower Thrips,Frankliniella occidentalisPergande (Thysanoptera: Thripidae)

Abstract: Host plant species will influence the population and physiological performance of insects. Frankliniella occidentalis is a well-known invasive pest commonly found on flowering plants. Herein, the population development of F. occidentalis was investigated on the flowers of different Rosa chinensis cultivars (Ruby, Love, Parade, Pink Peace, and Mohana), and the digestive enzyme activities in thrips were measured after feeding on these flowers. The developmental times of F. occidentalis from egg to adult were 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Shen et al [ 27 ] found that pollen of rose, camellia, rape, and 10% sucrose solution could promote oviposition in WFT. Recently, Qi et al [ 28 ] found that rose species could influence the population and physiological performance of WFT, and that digestive enzymes might play an important role in nutrient metabolism and growth of thrips. Earlier studies have tested the flower promotional effect on WFT.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al [ 27 ] found that pollen of rose, camellia, rape, and 10% sucrose solution could promote oviposition in WFT. Recently, Qi et al [ 28 ] found that rose species could influence the population and physiological performance of WFT, and that digestive enzymes might play an important role in nutrient metabolism and growth of thrips. Earlier studies have tested the flower promotional effect on WFT.…”
Section: Introductionmentioning
confidence: 99%
“…The type of host plants, different parts of host plants, and presence or absence of flowers affect the ecological, physiological, and biochemical characteristics of thrips ( Agrawal et al 1999 , Gerin et al 1999 , Mouden et al 2017 ). Some studies have reported the responses of digestive enzymes of WFTs to feeding on different vegetables and flowers ( Zhi et al 2021 , Qi et al 2022 ), and their population burst has closely been associated with the blooming of flowers ( Sun et al 2011 ). Therefore, we hypothesized that the nutrient contents of rose flowers, pollen, and nectar affect the nutrient contents of WFTs and their digestive enzyme activities, which could contribute to their feeding choice, physiological metabolic mechanism, and population dynamics.…”
Section: Introductionmentioning
confidence: 99%